-8x+7=7x+11

Simple and best practice solution for -8x+7=7x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8x+7=7x+11 equation:


Simplifying
-8x + 7 = 7x + 11

Reorder the terms:
7 + -8x = 7x + 11

Reorder the terms:
7 + -8x = 11 + 7x

Solving
7 + -8x = 11 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
7 + -8x + -7x = 11 + 7x + -7x

Combine like terms: -8x + -7x = -15x
7 + -15x = 11 + 7x + -7x

Combine like terms: 7x + -7x = 0
7 + -15x = 11 + 0
7 + -15x = 11

Add '-7' to each side of the equation.
7 + -7 + -15x = 11 + -7

Combine like terms: 7 + -7 = 0
0 + -15x = 11 + -7
-15x = 11 + -7

Combine like terms: 11 + -7 = 4
-15x = 4

Divide each side by '-15'.
x = -0.2666666667

Simplifying
x = -0.2666666667

See similar equations:

| 18=-4a | | 10u-4u+9t-2t= | | -w+4[w+3]=-12 | | 60-2(2x-2)=4(x+2)+6x | | (x-1)(6x+2)=(2x+8)(3x-6) | | -(5x-5)-(6x-5)+9=-9(x-1)-(5x+8)+3 | | 2+4X=4-(x-3) | | 2[m+1]=16 | | =364x | | 9e+4e+7f+2f= | | 6x^2+18xy^2-24xy= | | 25x=150-65 | | 13+2[5c-2]=29 | | 14+3x=3+5x+4 | | x^3+10x^2+33x+36=0 | | 2x^2+2y^2+2xy+10x+2y+14=0 | | 8x-(1-5x)=17+7x | | 2(x+10)=7(x+2)-4x | | f(x)=x^3+10x^2+33x+36 | | 105-x-40+3x=150 | | 7c-4=7 | | 3x+12=(x+1) | | 105-35-40+60=150 | | (x+1)(x-6)=(x+5)(x-2) | | 4x-2x=3(x-3) | | 16x^3-28x^2+4x=-8x | | 7x-11=5(x-2)+2x | | x^3+2x^2=80x | | 7(3n-3)=(7n+7)+4 | | 5x+7=.5(10x+12) | | 5x+7=1.2(10x+12) | | 35(3-x)-20(2-3x)=150 |

Equations solver categories